(3fHP hZQGFH eeG PcQg Gdabjg GdCOjH GHf LHjQ aj QMdJg GdMLGRjI hhLgJg GdeTQbjIs - (3GHf LHjQs
(3ChdgG (B:s
(3bGd (B: (3PcQ eG TGgOfG ef CNHGQ GdCScfOQjI hBKGQgG s
(3BNQgG (B:s
(3PcQ GdeTGgO GdecQeI GdJi HHbjY GdZQbO hHSaM LHd BNQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(488/3) s
Keywords: (3GdLZQGajG h GdHdOGfs